119구급대의 어려운 기관내삽관 교육 전·후 비교 - 윤형완; 유은영; 윤영현; Yun, Hyeong-Wan; Yu, Eun-Yeong; Yun, Young-Hyun (한국콘텐츠학회 논문지, 11(1), 2011)
The purpose of this study was to examine the effect of difficult endotracheal intubation education in the 119 rescue services. The subjects in this study were 60 members of the 119 rescue services that was under the umbrella of the Fire Service Headquarters of J province. A SPSS 14.0 program was utilized to find out the effect of tough tracheal intubation education on their relevant knowledge, self-confidence, academic self-efficacy and technical Performance in consideration of general characteristics. The findings of the study were as follows: 1. They showed a significant improvement in all the knowledge, self-confidence, academic self-efficacy and technical Performance after they received that education. 2. As for connections between general characteristics and knowledge before and after that education, there were significant differences in their knowledge according to gender and career of working in the hospital, and their rank and career of working in the hospital made a significant differences to their self-confidence. Their academic self-efficacy significantly differed with rank, career of working in the hospital and academic credential. There were significant gaps among them technical Performance Case 1 according to career of working in the 119 rescue services, and technical Performance Case 2 significantly varied with age and academic credential. There were significant gaps in technical Performance Case 3 according to career of working in the 119 rescue services and career of working in the hospital after that education was provided, and technical Performance Case 4 significantly varied with age and rank before and after the education was conducted. In conclusion, the kind of education programs that aim at stirring up the interest of the 119 rescue services in advanced airway and helping the members learn about tracheal intubation accurately with confidence is urgently required. 본 연구는 J도 소방안전본부 산하 119구급대 60명을 대상으로 하였으며, 연구 기간은 2009년 12월 1일 부터 2월 10일까지였다. 어려운 기관내삽관 교육 전.후 비교 및 일반적 특성에 따른 지식, 자신감, 학업적 자기효능감, 술기수행 능력을 SPSS 14.0을 이용하여 분석한 결과는 다음과 같다. 1. 지식, 자신감, 학업적 자기효능감, 술기수행 능력 모두 교육 전보다 교육 후 유의미하게 증가하였다. 2. 일반적 특성에 따른 교육 전 후 지식은 성별과 병원근무경력에서 모두 유의한 차이를 보였고, 자신감은 계급과 병원경력에서 모두 유의한 차이를 보였다. 학업적 자기효능감은 계급과 병원경력 및 학력에서 모두 유의한 차이를 보였다. 술기수행 능력은 유형 1에서 119구급대 근무경력, 유형 2에서는 대원의 연령과 최종학력이 유의한 차이를 보였으며, 유형 3은 119구급대 근무경력과, 병원에서 근무경력이 교육 후 유의한 차이를 보였다. 유형 4는 연령과 계급에서 교육 전 후 유의한 차이를 보였다. 결론적으로, 119구급대의 기도유지술에 관심을 갖고, 정확한 기관내삽관을 배울 수 있도록 자신감을 함양시킬 수 있는 교육 프로그램이 절실히 필요하다고 사료된다.